Teachers’ Perspectives on Students’ Conceptual Difficulties in Magnetism: Challenges and Instructional Implications - Basri, Nur Akhyar; Kusairi, Sentot; Sunaryono; Irawan, Ivan Danar Aditya; Sanusi, Dirga Kaso (Jurnal Pendidikan Fisika, 2025)
Magnetism is a fundamental component of physics education that underpins both scientific literacy and technological innovation. Yet, research consistently shows that students struggle to achieve a deep conceptual understanding of this topic. Persistent misconceptions, particularly in visualizing three-dimensional vector relationships and applying the right-hand rule, hinder students’ ability to transfer knowledge to novel contexts. Addressing these difficulties requires not only innovative instructional media but also insights from teachers who directly observe and manage such challenges in classroom practice. This study aimed to explore high school physics teachers’ perspectives on the difficulties of teaching magnetism and their interpretations of students’ learning barriers. Using a qualitative descriptive design, data were collected through semi-structured interviews with three teachers from different regions of Indonesia, each with four to seven years of teaching experience. Thematic analysis of the interview transcripts revealed two major findings: teachers reported significant limitations in instructional resources, which restricted their ability to dynamically depict vector orientations and forces; and students were observed to rely on rote memorization, struggle with spatial visualization, and confuse the applications of the right-hand rule in different contexts. These results highlight the intersection of pedagogical and cognitive barriers, showing how inadequate media directly contributes to persistent student misconceptions. The novelty of this study lies in foregrounding teachers’ experiences, thereby filling a gap in the literature that has predominantly focused on student-centered analyses. The conclusions emphasize the need for interactive, spatially explicit media, supported by structured pedagogical guidance, to strengthen magnetism learning. This study contributes to physics education by integrating teachers’ perspectives into efforts to design feasible and effective instructional interventions.